Anoxic oceanic conditions during the late Permian mass extinction-evidence from the Chutani formation, Bolivia. (November 2020) - Nina, L.; Paula-Santos, G.M.; Sial, A.N.; Bark, G.; Wanhainen, C.; Jiménez, G.; Blanco, M.
Abstract: We analyze diagenesis of carbonate rocks from the Late Permian Chutani Formation of western Bolivia (San Pablo de Tiquina section) in the southern Lake Titicaca zone, which is a sedimentary succession of semiarid tidal flat comprised of mixed carbonate and siliciclastic units. The diagenetic study includes petrographic analysis (conventional petrography and cathodoluminescence) and geochemical analysis (carbon and oxygen isotopes and minor element chemistry). An integrated study of lithofacies and isotope stratigraphy of carbonates shows a succession of five types of depositional environments: tidal barrier, tidal flat, shoal coastal and shoreface. The Chutani Formation was subjected to different diagenetic processes including micritization, cementation, mechanical compaction, dissolution, neomorphism, dolomitization and dedolomitization that occurred during marine to shallow burial stages. Carbon isotope (δ 13 C) values range between −7 and 2.9‰ (VPDB) with variations linked to stratigraphic changes. The transgressive stage of the basin exhibits an upwards decreasing trend of δ 13 C values whereas regression is marked by an increase in such values. The oxygen isotope values (δ 18 O) vary from −16.6 to −1‰ VPDB with lighter values towards the top of the stratigraphy. The transgressive trend may reflect mixing of meteoric water and/or volcanic-hydrothermal fluids with seawater or progressive oxygenation with enhanced circulation conditions. Heavier values during regression may reflect more evaporitic and anoxic conditions towards the Permian-Triassic boundary. Significant variation in isotope values among neighbouring samples is observed, especially during trangression, which may be the result of different diagenetic processes. Highlights: The transgressive of the basin exhibits an upwards decreasing trend of δ 13 C values while regression is marked by an increase. The negative δ 13 C shifts are caused by meteoric, volcanic or hydrothermal fluid interaction with rock. Significant variation in isotope values among neighbouring samples, especially during transgression. Heavier values during regression may reflect more evaporitic and anoxic conditions towards the Permian-Triassic boundary.